Peran Pendidikan Islam Dalam Mensiasati Khilafiyah - Abu Darda (At-Ta'dib, 2016)
Islamic education is the best strategy to resolve social conflicts ofkhilafiyah that occurred in the Muslim community. This paper aims toexplain how to address khilafiyah through Islamic Education. Study ofliterature with this a critical analysis method found that khilafiyah doesnot need to be removed because it is the sunnatullah, that is the consequencesof ijtihad. What needs to be carried out by Muslims is how to managekhilafiyah into something constructive in social life. Khilafiyah should beviewed as a wisely, tolerantly and full of brotherhood and peace. Thisperspective on khilafiyah can grow by developing social ethics, such asIslamic education. As a result, Islamic education must be willing to get areconstruction in its various aspects; such as the theological andphilosophical aspects, substantive aspects, methodological aspects, and theethical aspects of nation and state.